Momentos De Silencio, Serie 1-8. - Juan Carlos Orrantia. (Antípoda: Revista de Antropología y Arqueología, 2009)
This photographic series, more than a specific documentation, seeks to explore the potential of the medium to generate questions about the invisibility and the silences that converge in the daily life of those living in the aftermath of terror. Based on portraits and moments taken during yoga sessions with internally displaced persons and former combatants, I reflect on the idea of the body as an agent that suggests and remembers subjective conditions and historical trajectories that nurture the present context, even if most of them tend to dissipate within common sense. This allows me to engage the relationship between photography and representations within the contexts of the production of normalcy in the aftermath of terror.